Efektivitas Metode Bernyanyi terhadap Kemampuan Fonasi Mahasiswa - Samsul Anam; Dewi Lestari; Awalludin Awalludin (LP4MK STKIP PGRI Lubuklinggau, 2020)
The purpose of this study was to determine the effectiveness of the singing method on students' phonation abilities. The method used is an experimental method with a pre-experimental model design one group pretest-posstest. Data collection techniques using essay test techniques. The sample in this study was class A.2.1 with a total of 39 students. The data analysis used the t test formula using the IBM SPSS 24 program. The results showed that the singing method was effective in improving students' phonation skills in the Phonology course. The effectiveness of this singing method was proven by the results of the pretest with the student's average score of 83.7 with a very good category, while the posttest results of 85.4 were also in a very good category. Based on the results of statistical test analysis using SPSS 24, it can be explained that the average value obtained is 1.65 with a standard deviation of 14.391, and the average standard error value is 2.433. From the results of the data analysis, the t test value is 3,970 with a df of 34.